Trichoderma and Phosphite Elicited Distinctive Secondary Metabolite Signatures in Zucchini Squash Plants - Luigi Formisano; Begoña Miras-Moreno; Michele Ciriello; Christophe El-Nakhel; Giandomenico Corrado; Luigi Lucini; Giuseppe Colla; Youssef Rouphael (Agronomy, 2021)
Plant biostimulants are “green” solutions to improve crop production. Trichoderma spp. and phosphites, ordinarily used as biocontrol agents, can trigger phytostimulation, also promoting endogenous mechanisms involved in plant growth and development. The present study aimed at assessing the efficacy of a phosphite-based formulation (Phosphit-One) and Trichoderma harzianum-T22 on the morpho-physiological response and modulation of the metabolomics profile in zucchini squash plants (Cucurbita pepo L.) cultivated in controlled growth conditions (Fitotron®). The highest values of fresh biomass production (390.9 g plant−1) and root dry weight (5.6 g plant−1) were obtained for Trichoderma-treated plants. This last treatment resulted in an improved physiological performance (SPAD index, CO2 assimilation rate, and Fv/Fm ratio) measured 30 days after transplanting. Both Trichoderma and phosphite treatments induced a broad metabolic reprogramming in leaves, evident also for the phosphite treatment that did not result in a growth promotion. The microbial and the non-microbial treatments showed distinctive signatures in secondary metabolism yet, common responses could be also highlighted. For instance, both Trichoderma and phosphite triggered ROS-mediated signaling processes, together with the accumulation of phenylpropanoids, glucosinolates, and phytoalexins. Furthermore, a significant alteration of phytohormones was observed, with terpenoid gibberellins and brassinosteroids showing the largest differences. The metabolomic signatures induced by Trichoderma and phosphite in zucchini squash provided molecular insights into the processes underlying elicitation of plant defense due to biostimulation. Interestingly, the modulation of plant secondary metabolism by both treatments did not impair plant growth.